Design and Algorithm Research of a Weight Sorting Transport Robot - Du, Haojie; Yang, Guang; Pei, Lele (Manufacturing Technology Journal, 2023)
In warehousing logistics, the sorting and transportation efficiency of goods is still one of the important factors limiting the rapid development of logistics. At present, most regions still use manual sorting with low efficiency and high cost. Especially in some special work areas, such as high temperatures, severe electronic radiation, and areas with heavy long-term work tasks, urgent need for small robots to replace manual labor. In order to solve the inconvenience that small places such as logistics only use manual sorting, It is necessary to design a small-sized weight sorting and transportation robot, which can wait for receiving goods at a designated location, judge and identify the weight of goods by itself through PID intelligent control algorithm, which can move forward at a constant speed, and transport its weight to the designated position and unload it. Constant speed can make the trolley travel more smoothly and load and unload goods more smoothly, which is of great significance.
Keywords: STC; Weight sorting transportation; PID; Adaptive algorithm